In-situ chlorophyll fluorescence and related growth of white Guinea yam at different ages - Aighewi, B.A.; Ekanayake, I.J. (Wiley, 2004)
Leaf chlorophyll photochemical attributes and growth of two cultivars of white Guinea yam (Dioscorea rotundata) were examined. The photochemical efficiency (Fv/Fm ratio) of cv. Pepa was significantly higher than that of cv. Abi at 10, 14 and 22 weeks after transplanting (WAT). The peak photosynthetic efficiency period for both cultivars was at 18 WAT. Leaf area indices and crop growth rate were greater for Pepa than Abi, as was the leaf transpiration rate. During peak growth periods Pepa was less stressed than Abi according to midday leaf water potentials and stomatal conductance.